Olanzapine induced tardive dyskinesia treated successfully with quetiapine: A case report - Ugurlu, Gorkem Karakas; Bilici, Rabia; Ugurlu, Mustafa; Tufan, Evren; Saglam, Sadullah (Pergamon-Elsevier Science Ltd, 2011)
[Abstract Not Available]